Four dimensions of quality in Australian jobs - Ribar, David; Wooden, Mark (My University, 2020)
We develop and analyse comprehensive, multi-item scales of the quality of Australian jobs, using the rich measures of job characteristics from the Household, Income and Labour Dynamics in Australia Survey. Through exploratory methods and multidimensional item response theory modelling, we uncover four gender-specific scales that describe the autonomy, demands/engagement, compensation adequacy and security of jobs. From 2001 to 2016, women’s job demands/engagement and compensation adequacy grew noticeably, and men’s job demands/engagement grew somewhat. Since the mid-2000s, job security has fallen for both women and men. Job quality rises with job tenure, work experience and health, and falls following involuntary job changes.
The Economic Record
Keywords: Labour market